2017
DOI: 10.15407/ukrbotj74.03.248
|View full text |Cite
|
Sign up to set email alerts
|

Invasive aquatic macrophytes of Ukraine

Abstract: Natural and historical reasons, mechanisms of expansion as well as ecological and coenotic peculiarities of model alien aquatic macrophytes such as Azolla cristata, A. filiculoides, Elodea canadensis, E. nuttallii, Vallisneria spiralis, Egeria densa, Pistia stratiotes, Phragmites altissimus and Zizania latifolia in Ukraine's reservoirs are discussed. It is established that at present Pistia stratiotes and Egeria densa are the most dangerous for hydrotopes. The mentioned species have wide ecological ranges and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
4
0
2
Order By: Relevance
“…Наводимо цей таксон як самостійний вид (Tikhomirov, 2021), хоча його систематика і номенклатура (зокрема, правильні назви в ранзі виду або підвиду) лишаються проблематичними і потребують подальших досліджень. В Україні на півдні Степової зони він, імовірно, є природним, але нині вже розповсюдився як адвентивний у більшості регіонів (Kuz, Starovoitova, 2014;Zvyagintseva, 2015;Dubyna et al, 2017;Bezsmertna et al, 2022;Orlov et al, 2022). У м. Київ (а також і в Україні в цілому) P. altissimus уперше було виявлено у 2011 р. на Оболоні, на березі оз.…”
Section: Papaver Stevenianumunclassified
“…Наводимо цей таксон як самостійний вид (Tikhomirov, 2021), хоча його систематика і номенклатура (зокрема, правильні назви в ранзі виду або підвиду) лишаються проблематичними і потребують подальших досліджень. В Україні на півдні Степової зони він, імовірно, є природним, але нині вже розповсюдився як адвентивний у більшості регіонів (Kuz, Starovoitova, 2014;Zvyagintseva, 2015;Dubyna et al, 2017;Bezsmertna et al, 2022;Orlov et al, 2022). У м. Київ (а також і в Україні в цілому) P. altissimus уперше було виявлено у 2011 р. на Оболоні, на березі оз.…”
Section: Papaver Stevenianumunclassified
“…Pistia stratiotes were detected in Ukraine back in the 80s of the last century, however, they did not pose a particular threat because they freezing in winter (Dubyna et al (2017). The development of local populations of the species was observed from time to time in decorative urban bodies of water (Odessa -2005, Kyiv -2009 (Lushpa 2009), they successfully overwintered and spread the following year.…”
Section: Brief Literature Review Of Species Invasions In Ukrainementioning
confidence: 99%
“…Thus, all confirmed locations of Elodea nuttallii within Ukraine are located in the Forest (Kyiv city) and the Forest-Steppe (Kyiv, Poltava and Cherkasy regions) nature zones. For the Steppe Zone, only one record from the mouth of the Danube River (Dubyna et al, 2017) was reported. A recent record of E. nuttallii in Sevastopol, Crimea was published (Svirin et al, 2021).…”
Section: лісові угрупованняmentioning
confidence: 99%
“…5 of the International Code of Phytosociological Nomenclature (Theurillat et al, 2021); besides, Elodea densa has previously never been found in the Lower Dnipro River. Dubyna with coauthors (2017) mentioned for Ukraine three associations (Polygono-Potametum natantis Soó 1957, Potametum lucentis Hueck 1931 and Potametum crispi Soó 1927) with E. nuttallii as an attendant species, and two syntaxa with E. nuttallii as a diagnostic and characteristic taxon -Elodeetum nuttallii Ciocorlan et al 1997and Ceratophyllo demersi-Elodeetum nuttallii Ciocorlan et al 1997(Dubyna et al, 2017. However, these two syntaxa described from Romania have not been listed in the Prodrome of the vegetation of Ukraine Thus, our results confirmed the distribution of the alien aquatic species Elodea nuttallii in the Lower Dnipro River (Kherson Region).…”
Section: лісові угрупованняmentioning
confidence: 99%